2020
DOI: 10.1042/bsr20201491
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of immune-related genes in high and low tumor mutation burden groups of chromophobe renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is one of most common cancer with gradually increasing incidence and high mortality. chromogenic RCC (chRCC) is the third most common histological subtype of RCC, accounting for about 5-7% of RCC. In our study, the transcriptome expression profile data (n=89) of chRCC, corresponding clinical data (n=113) and the somatic mutation data (n=66) was obtained from the TCGA database. We first analyzed the mutation data of chRCC patients and divided chRCC patients into high and low tumor mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Human gene PDGFRL (platelet-derived growth factor receptor–like protein) underexpression reduces tumor mutation burden [ 67 ], thus raising reproductive potential consistently with the cavy ortholog expression alteration during microevolution [ 29 ], whereas a PDGFRL excess leads to hypertensive behavior and myocardial hypertrophy [ 68 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Human gene PDGFRL (platelet-derived growth factor receptor–like protein) underexpression reduces tumor mutation burden [ 67 ], thus raising reproductive potential consistently with the cavy ortholog expression alteration during microevolution [ 29 ], whereas a PDGFRL excess leads to hypertensive behavior and myocardial hypertrophy [ 68 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous clinical trials in multiple tumors have also shown that there is a positive correlation between TMB and the e cacy of PD-1/PD-L1 inhibitors and a trend toward longer PFS(47-49). Li et al found that a high TMB was signi cantly associated with a worse prognosis and could promote tumor metastasis and development (50). Our results showed that the presence of F. nucleatum in tumors and the TMB could be combined to predict postoperative metastasis in esophageal cancer.…”
Section: Discussionmentioning
confidence: 51%
“…TMB is a new type of biomarker for cancers, which has proven e cacy in a variety of cancers, such as breast cancers, lung cancers, and colorectal cancers. Li et al [14] found that high-TMB was associated with a worse prognosis, and it could promote tumor metastasis and development in patients with chromophobe cell carcinoma (chRCC). Zhang et al [15] also reported that, the high-TMB patients showed poorer survival results, higher pathological stages and higher tumor grade in patients with clear renal cell carcinomas when compared with the low-TMB group.…”
Section: Discussionmentioning
confidence: 99%